A novel hybrid binary reconstruction algorithm for ultrasonic tomography - Abdul Rahim, R.; Fazalul Rahiman, M. H. (International Frequency Sensors Association (IFSA), 2008)
This paper presents a novel image reconstruction algorithm namely the Hybrid Binary Reconstruction Algorithm (HBRA). The algorithm is capable to improve the noise in the conventional back-projection based algorithm. The comparison between the Linear Back Projection Algorithm (LBPA) and the Hybrid Binary Reconstruction Algorithm have been made. The results are positive and are presented at the end of the paper.